A Marine Natural Product, Harzianopyridone, as an Anti-ZIKV Agent by Targeting RNA-Dependent RNA Polymerase - Kexin Zhang; Jingyao Liang; Bingzhi Zhang; Lishan Huang; Jianchen Yu; Xuhan Xiao; Zhenjian He; Huaming Tao; Jie Yuan (Molecules, 2024)
The Zika virus (ZIKV) is a mosquito-borne virus that already poses a danger to worldwide human health. Patients infected with ZIKV generally have mild symptoms like a low-grade fever and joint pain. However, severe symptoms can also occur, such as Guillain-Barré syndrome, neuropathy, and myelitis. Pregnant women infected with ZIKV may also cause microcephaly in newborns. To date, we still lack conventional antiviral drugs to treat ZIKV infections. Marine natural products have novel structures and diverse biological activities. They have been discovered to have antibacterial, antiviral, anticancer, and other therapeutic effects. Therefore, marine products are important resources for compounds for innovative medicines. In this study, we identified a marine natural product, harzianopyridone (HAR), that could inhibit ZIKV replication with EC50 values from 0.46 to 2.63 µM while not showing obvious cytotoxicity in multiple cellular models (CC50 > 45 µM). Further, it also reduced the expression of viral proteins and protected cells from viral infection. More importantly, we found that HAR directly bound to the ZIKV RNA-dependent RNA polymerase (RdRp) and suppressed its polymerase activity. Collectively, our findings provide HAR as an option for the development of anti-ZIKV drugs.